Akselerasi Pemahaman Mahasiswa Melalui Pengembangan Media Pembelajaran Holografi Multi Bahasa Mata Kuliah Konsep Pendidikan Seni - Iriaji; Abdul Rahman Prasetyo; Purnomo; Alby Aruna; Mohamad Firzon Ainur Roziqin; Eka Putri Surya; Adinda Marcelliantika (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to accelerate student understanding in the course of Art Education Concepts through the development of multilingual holographic learning media. This approach utilizes hologram technology to present learning materials in a visual and interactive manner, supporting more effective concept comprehension. The methodology employed is a development design, beginning with an analysis of student needs followed by the design, implementation, and evaluation of the holographic learning media. The study involved students from various language backgrounds, testing the effectiveness of the media in supporting cross-language understanding. Results show significant improvements in students' comprehension of art education concepts, as evidenced by pretest and posttest assessments. The holographic learning media offers significant potential in art education, providing an immersive learning experience accessible to multilingual students. This research provides new insights into the use of advanced technology for art education.